Entrevista a Suniyay Moreno, autora del libro de literatura infantil La hermana menor - Polastri, Vanesa (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2024)
Picturebooks serve as mirrors, windows and sliding glass doors (Bishop, 1990). However, minoritized groups do not often see their reflection in them and, when they do, it is generally distorted or biased, as such representation is elaborated by those in dominant groups. Finding a book whose story reflects an indigenous culture from the Argentinian territory and which was written by a descendant of that cultural group allowing room for Quichua, her native language, is a treasure for any teacher who embraces diversity. Through the present interview the readership will be able to get to know Suniyay Moreno, this debut author; her children’s literature picturebook: “La hermana menor”, that merges Spanish and Quichua; its translation into English; and the value of both versions to be exploited in the language class from an intercultural and translingual approach.